2015
DOI: 10.1086/681717
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Quantitative Traits under a Migration-Selection Balance: When Does Skew Matter?

Abstract: Quantitative-genetic models of differentiation under migration-selection balance often rely on the assumption of normally distributed genotypic and phenotypic values. When a population is subdivided into demes with selection toward different local optima, migration between demes may result in asymmetric, or skewed, local distributions. Using a simplified two-habitat model, we derive formulas without a priori assuming a Gaussian distribution of genotypic values, and we find expressions that naturally incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…6 of 14 quantitative traits in this study) or traits evolving under migration‐selection balance (Débarre et al . ). Unfortunately, an appropriate model also capable of accounting for this study design does not yet exist.…”
Section: Discussionmentioning
confidence: 97%
“…6 of 14 quantitative traits in this study) or traits evolving under migration‐selection balance (Débarre et al . ). Unfortunately, an appropriate model also capable of accounting for this study design does not yet exist.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, when loci contribute unequally to trait variation, the shape of the phenotypic distribution may depart from normality, and become skewed, or have higher kurtosis. For example, Débarre, Yeaman & Guillaume () showed that when traits are affected by a few loci of large effect (i. E. major loci) together with many loci of small effect (i. E. minor loci), they are better able to resist homogenization by gene flow and lead to better local adaptation under diversifying selection between divergent habitats than when only minor loci are considered. In Débarre et al .…”
Section: Representation Of Dispersal Genetics In Modelsmentioning
confidence: 99%
“…When there is substantial variation in the effect sizes of alleles, the distribution of breeding values in populations experiencing local adaptation and recurrent migration can become skewed, sometimes strikingly, as Florence Débarre, Sam Yeaman, and Fred Guillaume show in this issue (Débarre et al 2015). This is caused by the interaction of local selection and migration, as a result of which the descendants of recent migrants can be far from the local mean.…”
mentioning
confidence: 99%